Evaluation of Oxytetracycline Metabolites Cross-Reactivity with Oxytetracycline Enzyme-Linked Immunosorbent Assay (ELISA) - Faraj Hijaz (Antibiotics, 2020)
Antibiotics have been successfully used for the control of several plant diseases for many years. Recently, streptomycin and oxytetracycline have been approved for the treatment of Huanglongbing (HLB) in Florida. The enzyme-linked immunosorbent assay (ELISA) is the most commonly used assay for the detection of these antibiotics because it is quick, simple, and can be used to analyze many samples at the same time. However, ELISA can react with the metabolites of the parent compound and its structurally related compounds. In this study, we investigated the cross-reactivity of the oxytetracycline ACCEL ELISA kitTM with three of oxytetracycline metabolites (4-epi-oxytetracycline, α-apo-oxytetracycline, and β-apo-oxytetracycline). The α-apo-oxytetracycline and β-apo-oxytetracycline metabolite did not show any cross-reactivity in the linear range (1.5–50 ng mL−1) of the assay. Whereas 4-epi-oxytetracycline showed high cross-reactivity, and its response was similar to oxytetracycline. Our results indicated that the oxytetracycline ELISA kits estimate the level of oxytetracycline as well as its main metabolite, 4-epi-oxytetracycline.